الأمن الوطني وصنع القرار في الوطن العربي في ظل التحديات الجيوسياسية لتغير المناخ - فيصل وفاء كامل (Tasnim International Journal for Human, Social and Legal Sciences, 2026)
The Climate change represents one of the most pressing challenges facing the Arab region in the twenty-first century, not only at the environmental level but also at the political and security levels. The changing climate, accompanied by phenomena such as desertification, water scarcity, and rising temperatures, does not stop at impacting natural resources alone; it also extends to affect internal stability and political decision-making processes within states. Given the fragile environmental and economic structures in many Arab countries, climate change becomes a multiplier of crises, exacerbating issues of food and water security and placing additional pressures on governments in managing their limited resources This research aims to examine the implications of climate change from the perspective of political geography, with a particular focus on how it influences national security and the formulation of public policies in the Arab world. The study addresses several key themes, including the impact of water scarcity on political and security decisions, the role of environmental changes in intensifying migration flows and local conflicts, and the challenges imposed by the geographical position of Arab states within the broader context of global climate change Furthermore, the research seeks to provide an analytical reading of selected Arab case studies—such as Iraq, Egypt, and the Gulf states—in order to illustrate how climate change differentially affects political decision-making depending on varying geographical and economic conditions. The study concludes that confronting climate-related challenges requires the integration of environmental considerations into security policies and strategic planning, thereby strengthening the resilience of Arab states against crises and ensuring their stability within an increasingly dynamic regional and international environment.